ВЛИЯНИЕ УЛЬТРАЗВУКОВОГО ОБЛУЧЕНИЯ НА РЕКОМБИНАЦИОННЫЕ ПАРАМЕТРЫ В СТРУКТУРЕ Al-Al2O3–p-CdTe-Mo - Утениязов, А.К.; Даулетмуратов, Б.К.; Нсанбаев, М.Т.; Асанова, А.Т. (SCIENCE and SOCIETY, 2021)
In the article investigates the effect of ultrasonic irradiation (UST) on the recombination parameters in the Al-Al2O3–p-CdTe-Mo - structure. It was found that the recombination of nonequilibrium carriers in such a structure occurs through complex pair recombination complexes and, as a result of ultrasonic treatments, the number of both small acceptors and deeprecombination centers increases.